3-D Numerical Modelling Of Cakar Ayam System To Maximize It’s Stability Performance - Agus Sulaeman; Sajiharjo Marto Suro; Salihin bin Jalali (Program Studi Teknik Sipil, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2021)
This paper presents an analysis of Cakar Ayam system using the finite element method. The basic concept of the Cakar Ayam system considers the passive-soil pressure creating a stiff condition of slab-pipe system. This means that the thin concrete slab floats on the supporting soil and the pipes serve as stiffeners slab concrete, stay vertical due to the passive-soil pressure. In this study, the simulation was done to the stiffness ratio of 0.02 to 1.2 under soil friction angle 20 o , bearing capacity and displacement were recorded for each pairs then plotted in the graph.The study was intended to illustrate the basic mechanism of the Cakar Ayam system. Two cases have been considered for the parametric studies. The parameters investigated are thickness of slab and diameter of pipes. It is shown that such a Cakar Ayam system improves the behaviour of the raft foundation. It is also found that all the parameters used in the parametric studies influence the behaviour of the Cakar Ayam system.